The combined effects of shear stress and mass transfer on the balance between biofilm and suspended cell dynamics - Joana Moreira (2015)
This work investigates the effect of shear stress and mass transfer on the development of biofilms in a flow cell that mimics industrial piping. The shear stress and maximum flow velocity were estimated by computational fluid dynamics and the external mass transfer coefficient was calculated using empirical correlations for Reynolds numbers ranging from 100 to 10,000. The effect of two flow rates on the development of Escherichia coli biofilms under turbulent flow conditions was assessed and it was observed that biofilm formation was favored at the lowest flow rate. Additionally, estimations of the shear stress and external mass transfer coefficient indicate that both parameters increase with increasing flow rates. Thus, it seems that biofilm formation was being controlled by the shear stress that promoted biofilm erosion/sloughing and not by mass transfer which would potentiate biofilm growth. Our results indicate that not only efficient pre-treatment units are required on water recirculation loops in order to reduce the effective concentration of bacteria and nutrients, but also that high flow rates are preferred at all times to reduce the buildup of bacterial biofilms. For instance, high flow rates should be used during cleaning and disinfection cycles because the increase in shear stress will promote biofilm detachment and also potentiate the effect of biocides and other cleaning agents due to the increased mass transfer from the bulk solution to the surface of the biofilm.